Enhance Preparation and Characterization of Nickel-Oxide as Self-Cleaning Surfaces. (January 2019) - Haider, Adawiya J.; Al- Anbari, Riyad; Sami, Hiba M.; Haider, Mohammed J.
Abstract: In this work, manufacture of Nickel Oxide nano-particles (NiONP's) using sol-gel spin-coating method and deposited onto glass substrates as thin films. Nickel acetate was used as a starting material and annealed at different temperature (450°C, 550°C and 650°C).The structural, morphological, spectral and optical properties of synthesized NiONP's were characterized by X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR), Ultraviolet spectroscopy (UV-visible) respectively. Of the results, it was found that the crystallization of films develops strongly as the temperature of the annealing increases. Average particles size are range (15-30) nm. The thin films showed a higher optical transparency of thin films prepared at the beast annealing temperature 650C. Finally, Self-cleaning test were studies with and without UV lamp through important test hydrophicilty by measuring the Water Contact Angle results showed super-hydrophobicity properties